解構科學傳播：從地球暖化議題探討人際傳播如何中介大眾媒體的效果-解構科學傳播：從地球暖化議題探討人際傳播如何中介大眾媒體的效果（總計畫） - 李秀珠; LI SHU-CHU SARRINA (My University, 2013)
本整合計畫包含四個子計畫，所有子計畫都以全球暖化為研究的焦點，從人際傳播 的觀點探討大眾媒體傳佈全球暖化知識的效果如何被人際傳播所中介，但是四個子計畫 從不同的理論基礎來探討人際傳播如何中介大眾媒體的效果，子計畫一是從創新傳播的 理論觀點來探討全球暖化議題知識的傳佈，探討意見領袖接收了大眾媒體的全球暖化訊 息之後，不同的個人特質是否會影響其討論全球暖化議題的頻率及數量，並探討意見領 袖的人際傳播行為與全球暖化知識傳佈的相關性。子計畫二「人際交談與節能減碳行為 之採納：從對話分析取徑探討氣候變遷傳播效果」--這個子計畫是從「計畫性行為理論」 來探討人際溝通如何影響人們是否採取節能減碳的行為。「計畫性行為理論」 (theory of planned behavior, TPB) 主張，個人的行為意圖 (behavioral intention) 是決定個 人是否會採取行動的決定性因素，因為它是行為的心理前置變項，而行為意圖包括三個 元素：針對特定行為的態度、自覺社會壓力 以及促進或阻礙行動因素的自覺控制。子 計畫二以「計畫行為理論」為理論基礎，探討「重要他人」這個「社會身分」如何在與 人對話過程中，經由所有對話參與者的共同協商，成為影響民眾採行節能減碳行為的重 要因素；其次，針對「主觀規範」變項的論述性，本研究也希望了解，擁有「重要他人」 這個「社會身分」將如何影響「重要他人」表達反對意見？以及不同的表達方式是否會 影響交談對象採納節能減碳行為的行為意圖？子計畫三「網路社群媒體參與形式、動機 導向體驗與網路使用者對地球暖化議題之理解及參與」，子計畫三採用媒介參與感 (media engagement, Calder & Malthouse, 2008) 理論，觀察網路使用者如何形成不同的參 與形式。根據創新傳布及兩級傳播研究傳統，本研究想瞭解具有創新傾向的網路使用者 是否呈現正面的媒介參與感，而這些使用者是否可以成為網路社群的意見領袖，提升其 他網路使用者對地球暖化的理解及參與。子計畫四主要是以認知心理取向的兩個理論， 資訊效用理論及認知彈性理論，為分析架構，探討全球暖化議題網路資訊的標題、導言、 內容、結構、寫作風格乃至影音內容配搭，及其對閱聽人在相關議題的學習效果之影響。

The purpose of this integrated project is to examine the relationship between interpersonal communication and mass media effects with the issue of global warming as the focal point. This integrated project includes four projects that adopt difference theoretical frameworks and different approaches to investigate the same issues—the news of global warming. The first project using Rogers’ diffusion of innovation as the theoretical framework to study how interpersonal conversations mediate mass media effects on the news of global warming; the second project using the theory of planned behavior focuses on conversation analysis to understand how significant others affect the adoption of environment friendly actions; the third project is based on the theory of media engagement to investigate how to use different types of Internet social groups to affect users’ understanding of global warming news; the fourth project uses a cognitive approach to investigate the relationship between website designs and users’ understanding of global warming news. The four projects of this integrated project examine the relationship between interpersonal communication and mass media effects on the global warming news from different angels, and the research findings should allow scholars to better understand the relationship between mass media and interpersonal communication.
Deconstructing science communication: Examining the relationship between interpersonal communication and mass media effects on the issue of global warming in Taiwan
Keywords: 創新傳佈; 全球暖化; 網站設計; 人際傳播; 意見領袖; Global warming; interpersonal communication; mass media effects; opinion leaders; website designs.